The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/qai.0000000000003015
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Transmitted Infections Among Men and Transgender Women Using HIV Pre-exposure Prophylaxis in a Large Integrated Health System—A Cohort Study

Abstract: Background: Sexually transmitted infections (STIs) are common in people using pre-exposure prophylaxis (PrEP). We examined risk and factors associated with STIs in a cohort of PrEP users in an integrated health system in the United States.Setting: The Kaiser Permanente Southern California is a large integrated health system that provides comprehensive medical services to approximately 4.7 million demographically diverse members. Methods:We identified men and transgender women initiating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The follow-up of PrEP users in Brazil revealed an incidence of 19.1 cases of acquired syphilis per 100 person-years (95% CI 18.4-19.9). This incidence can be considered relatively high against results from other cohorts of PrEP users in Australia (9.4 (9.0-9.8) /100 PA) [16], Canada (1.94 (0.73-5.12) /100 BP) [13], and the United States (7.8 (7.1-8.4) /100 BP) [17], but similar to findings in Denmark (21.7 /100 BP) [18] and Spain (15.99 (11.94-21.41) /100PA) [19]. These regional disparities need to be better investigated.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The follow-up of PrEP users in Brazil revealed an incidence of 19.1 cases of acquired syphilis per 100 person-years (95% CI 18.4-19.9). This incidence can be considered relatively high against results from other cohorts of PrEP users in Australia (9.4 (9.0-9.8) /100 PA) [16], Canada (1.94 (0.73-5.12) /100 BP) [13], and the United States (7.8 (7.1-8.4) /100 BP) [17], but similar to findings in Denmark (21.7 /100 BP) [18] and Spain (15.99 (11.94-21.41) /100PA) [19]. These regional disparities need to be better investigated.…”
Section: Discussionmentioning
confidence: 92%
“…These findings may corroborate an increased vulnerability with the use of these substances. Hetcher et al [17] emphasizes that the relationship between the use of these substances and STIs needs to be examined more directly in order to understand the mechanisms that promote the vulnerability of individuals when they are using these substances. Indeed, understanding how these fragilities operate in the health-disease process for syphilis can facilitate management during PrEP to prevent this infection and other STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the open-label phase of DISCOVER also showed that PrEP users switching from TDF to TAF exhibited increase in eGFR (relative to baseline), while those who stayed on TAF had a relative decline [ 14 ]. However, the DISCOVER study population does not necessarily reflect the demographic characteristics of people on PrEP in the US [ 15 , 16 ], and it would be important to confirm findings in nontrial settings. In this retrospective cohort study using electronic health records (EHRs), we assessed changes in eGFR after switch from TDF to TAF in a matched cohort study where we compare TDF-to-TAF switchers to those who stayed on TDF.…”
mentioning
confidence: 99%